Exclusive Breastfeeding On Mothers' Knowledge And Attitudes In The Takalar District Health Center Work Area - Sudirman, Sudirman; Suardi, Yunita Suriani; Wati, Wati; Utari, Utari; Novianty, Natasha; Indriani, Putu Lusita Nati; Nainggolan, Nurcahaya (International Journal of Health Sciences, 2025)
The contents of breast milk include white blood cells, immune substances, digestive enzymes, hormones and proteins that are very suitable to meet the needs of babies up to 6 months old, breast milk contains carbohydrates, proteins, fats, multivitamins, water, carotene and minerals completely, which are very suitable and easily absorbed perfectly and do not interfere with the kidney function of babies who are growing. The purpose of the study was to determine the relationship between maternal knowledge and exclusive breastfeeding in the working area of the Takalar Regency Health Center. This research method is the Accidental Sampling technique. The instrument used in this study was a questionnaire sheet containing questions to obtain data. The statistical test used in this study is the Chi-square test using the Fisher's Exact Test alternative test which is a comparative test used on the data. The results of the study in table 1 show that the statistical test using the Chi-square test obtained a value of p = 0.005 (p <0.05 ) which means H1 is accepted or there is a significant relationship between maternal knowledge and exclusive breastfeeding. The conclusion obtained shows that there is a significant relationship between maternal knowledge and exclusive breastfeeding in the working area of the Takalar Regency Health Center.